Răspuns :
[(2/3)^2+1]^2÷13-(2 rad.2 +1)(2rad2-1)
[(4/9)+1]^2÷13-.....
formula de calcul prescurtat: (a+b)(a-b)=a^2-b^2=>
[(4/9)+1]^2÷13-(8-1)
in prima paranteza se aduce la acealsi numitor=>
(4+9/9)^2÷13-7
(13/9)^2-6
(169/81)-6
se aduce la acelasi numitor
169-486/81
−317/81
[(4/9)+1]^2÷13-.....
formula de calcul prescurtat: (a+b)(a-b)=a^2-b^2=>
[(4/9)+1]^2÷13-(8-1)
in prima paranteza se aduce la acealsi numitor=>
(4+9/9)^2÷13-7
(13/9)^2-6
(169/81)-6
se aduce la acelasi numitor
169-486/81
−317/81